Dose-Dependent Antidepressant-Like Effects of Cannabidiol in Aged Rats - Hernández-Hernández, Elena; García-Fuster, M. Julia (Frontiers in Pharmacology, 2022)
Aging predisposes to late-life depression and since antidepressants are known to change their efficacy with age, novel treatment options are needed for our increased aged population. In this context, the goal of the present study was to evaluate the potential antidepressant-like effect of cannabidiol in aged rats. To do so, 19-21 months old Sprague-Dawley rats were treated for 7 days with cannabidiol (dose range: 3-30 mg/kg) and scored under the stress of the forced-swim test. Hippocampal cannabinoid receptors and cell proliferation were evaluated as potential molecular markers underlying cannabidiol's actions. The main results of the present study demonstrated that cannabidiol exerted a dose-dependent antidepressant-like effect in aged rats (U-shaped, effective at the intermediate dose of 10 mg/kg as compared to the other doses tested), without affecting body weight. None of the molecular markers analyzed in the hippocampus were altered by cannabidiol's treatment. Overall, this study demonstrated a dose-dependent antidepressant-like response for cannabidiol at this age-window (aged rats up to 21 months old), and in line with other studies suggesting a beneficial role for this drug in age-related behavioral deficits.